HUBUNGAN C-ORGANIK TANAH TERHADAP SIFAT FISIK TANAH PADA PERTANAMAN SAWI PAKCOY DI DESA WOLOFEO KECAMATAN DETUSOKO KABUPATEN ENDE - Imaculata Fatima; Ermelinda Kue; Charly Mutiara (Agriculture Faculty of Flores University, 2021)
The production of mustard pakcoy (Brassica rapa L.) depends on the level of soil properties. Therefore, a study was conducted to determine the physical and chemical properties of the soil for mustard cultivation and its relationship. This research is quantitative descriptive. Observation variables in this study were C-organic soil, soil texture, soil moisture content, porosity, and bulk density. Laboratory data from soil physical properties and C-organic soil were matched with soil chemical criteria and evaluation of land suitability, After that, correlation analysis is used to see the relationship. The results showed that the C-organic content of the soil in Wolofeo Village was 3.01%-3.54% and was classified as high. While the physical properties of the soil in Wolofeo Village are for soil moisture content ranging from 39.77% -41.11%, Porosity ranges from 52.42% -61.33%, Fill Density ranges from 1.02 -1.26 g/ cm3, and the soil texture is sandy loam. These criteria are very suitable conditions for the cultivation of mustard greens. The relationship between C-organic soil and soil physical properties shows a significant relationship.